Z problematyki kary ograniczenia wolności w świetle nowelizacji kodeksu karnego - Sienkiewicz, Zofia (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In the present article the author examines the question of restriction of liberty in the light of the amended Criminal Code of 2015. In the new Civil Code restriction of liberty has become a means of a flexible response to a crime, making it possible to shape the severity of this penalty in a variety of ways. The amended provisions of the Criminal Code have considerably expanded the scope of its application, making it possible to impose this penalty not only in the case of petty and medium-severity but also serious offences. Restriction of liberty has become a penalty competing with fines and, above all, with suspended custodial sentence, the application of which, under the new provisions, should be considerably limited.
Keywords: kodeks karny; ograniczenie wolności; nowelizacja kodeksu karnego